Nanoparticle‐Mediated Suicide Gene Therapy for Triple Negative Breast Cancer Treatment. Issue 8 (11th May 2020) - Salvioni, Lucia; Zuppone, Stefania; Andreata, Francesco; Monieri, Matteo; Mazzucchelli, Serena; Di Carlo, Caterina; Morelli, Lucia; Cordiglieri, Chiara; Donnici, Lorena; De Francesco, Raffaele; Corsi, Fabio; Prosperi, Davide; et al.
Abstract: Systemic chemotherapy has not significantly reduced clinical demand for triple negative breast cancer (TNBC) treatments. To address the need for more effective therapy, the use of nonviral nanoparticles is explored to deliver suicide gene therapy as valuable alternative to protect nucleic acids in the bloodstream and improve their tumor uptake. Biocompatible cationic lipid nanoparticles are developed as a novel delivery system of a suicide plasmid gene encoding saporin. Active targeting is accomplished by taking advantage of nanoparticle functionalization with U11 peptide, designed to be directed toward urokinase plasminogen activator receptor, limiting off‐target toxicity. The antitumor effect of U11‐lipid‐protamine‐DNA (U11‐LPD) nanoparticles are tested in TBNC cells, showing a strong prevalence of targeted versus nontargeted nanoparticles in terms of uptake kinetics and proliferation inhibition. Transfection of green fluorescent protein (GFP) plasmid in MDA‐MB‐231 cells is demonstrated. U11‐LPD nanoparticles administered by retro bulbar injection exhibit excellent tumor tropism in TNBC orthotopic xenograft mice and effectively transfect TNBC cells with saporin plasmid resulting in tumor mass reduction. No systemic toxicity or organ damage is discovered after repeated treatments with nanoparticles. The findings suggest that systemic administration of targeted LPD nanoparticles to deliver saporin safely allows for active inhibition of cancer progression even in the absence of specific promoter gene sequences. Abstract : The use of biocompatible cationic lipid nanoparticles is explored to deliver suicide gene therapy (saporin‐encoding plasmid) against triple negative breast cancer. Targeting is accomplished via decoration with U11 peptide which is designed to target urokinase plasminogen activator receptor. The antitumor effect of U11‐lipid‐protamine‐DNA nanoparticles is tested in cancer cells. These nanoparticles exhibit tumor tropism resulting in cancer growth inhibition without systemic toxicity or off‐target organ damage.